Perfil de transmisión del SARS COV2 en una región sanitaria del Paraguay - Aguilar, Gloria; Estigarribia, Gladys; Méndez, Julieta; Morel, Zoilo; Ortiz, Ignacio; Ríos-González, Carlos; Baez, Teresita; Rojas de Arias, Antonieta; Schaerer, Christian; Muñoz, Sergio (Medicina Clínica y Social, 2023)
Introduction: Viral transmission often spreads in clusters, where infections can be traced to an index case or a geographic location, in order to take preventive measures in this regard, understanding the transmission profile of SARS-CoV-2 is essential. to develop effective disease prevention and control strategies.Objective: to determine the transmission profile of Sars-Cov-2, from clusters with identified index cases, in the V health region (Caaguazu) of Paraguay, between July and October 2020.Methodology: We carried out an observational, descriptive, cross-sectional study, with notification sheets of COVID-19 cases and laboratory results of the RT_PCR in patients diagnosed with COVID-19 in the V Sanitary Region betweenJuly and October 2020. .Results: We identified 703 people with positive Sars-Cov-2. 55.49% of people did not recognize any contagion link. Regarding the type of event where infections occurred most frequently, was in Social Events in 58.14% of the cases and the Family Environment in 33.89%, secondary transmission was observed in 17.40% of the cases. 58 Clusters were identified, with a median size of 3 (IQR 2-4), and 267 people (37.98%) associated with them.Conclusion: Most of the people did not recognize their contagion link, however, in those who did know, the main link was because they participated in social events , so it is essential to carry out this type of exercise to do timely follow-up. of the cases.